REGIONAL PLANNING AND DEVELOPMENT BASED ON DISASTER RISK REDUCTION IN BANTEN PROVINCE - Novian Andri Akhirianto (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2020)
Banten Province is one of the areas prone to disaster, because it has various hazards of disaster. On the other side, the process of regional development continues as well as all human activities. To handling these problems, disaster risk reduction efforts are needed by taking into account the regional developments. The purposes of this research are to identify the level of disaster risk, the level of regional development, and to find out the relationship between disaster risk and the level of regional development in Banten Province. This research was conducted using the literature study method, by searching and studying various literatures. Data analysis was performed using scoring techniques and an integrated model of the relationship between regional development and disaster risk, with the unit of analysis is district/ city. The results showed that there were 2 typologies of the relationship between disaster risk and regional development in Banten Province, 5 districts/ cities (Pandeglang Regency, Lebak Regency, Tangerang Regency, Serang Regency and Tangerang City) in typology I (high) and 3 districts/ cities (Cilegon City, Serang City, and Tangerang Selatan City) in typology III (low). Keywords: hazard, vulnerability, capacity, disaster risk, regional development, banten province.